1999
DOI: 10.1007/s001250051300
|View full text |Cite
|
Sign up to set email alerts
|

β-fibrinogen gene G/A-455 polymorphism in relation to fibrinogen concentrations and ischaemic heart disease in Chinese patients with Type II diabetes

Abstract: It has been increasingly recognised that the excess cardiovascular risk in Type II (non-insulin-dependent) diabetes mellitus could be partly contributed by an increased prothrombotic tendency, including increased fibrinogen concentrations [1], a strong predictor of ischaemic heart disease and stroke in various large epidemiological studies [2]. Fibrinogen and fibrin accumulate in the atherosclerotic plaque at a rate proportional to the plasma fibrinogen concentration [2,3]. Genetic factors which affect the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Although it did not reach statistical significance, MR score was lower in patients with left atrial thrombus. This study confirmed the higher prevalence of SEC in patients with LA thrombus (17,31).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although it did not reach statistical significance, MR score was lower in patients with left atrial thrombus. This study confirmed the higher prevalence of SEC in patients with LA thrombus (17,31).…”
Section: Discussionsupporting
confidence: 88%
“…However, these markers may change instantaneously, and they may also be affected by many other conditions. Recent studies revealed the relationship between beta-fibrinogen 455G/A polymorphism and stroke or myocardial infarction (17)(18)(19). Beta-fibrinogen 455G/A polymorphism was also shown to be associated with the increased erythrocyte aggregation and predisposing the development of stasis (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the latter were related to thrombosis in coronary arteries. However, 2 groups showed an association with the risk of cardiovascular disease in patients with non-insulindependent diabetes, 26,35 one with peripheral arterial disease, 32 one with deep venous thrombosis, 25 and the last one with large vessel cerebrovascular disease. 36 An additional study documented that the Ϫ455 G/A polymorphism was related to the progression of cardiovascular disease, in patients with hypercholesterolemia.…”
Section: Fibrinogen Polymorphisms and Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…15,16 Only few studies have found an association between Ϫ455 G/A polymorphism and the risk of ischemic vascular disease (Table). 25,26,32,35,36 In particular, out of 14 studies in which the relation between Ϫ455 G/A polymorphism and the risk was evaluated, only 5 reported the presence of an association. None of the latter were related to thrombosis in coronary arteries.…”
mentioning
confidence: 99%